Ethnic Differences in Myopia: Axial Length and Central Corneal Thickness in the Minang Population - Pratama Yogi; Wati Rinda; Hendriati; Hidayat Muhammad; Ariesti Andrini; Helvinda Weni (HM Publisher, 2025)
Background: Myopia is a prevalent vision disorder characterized by blurred distance vision. It is often associated with increased axial length (AL) and alterations in central corneal thickness (CCT). This study investigated the relationship between AL and CCT in individuals from the Minang ethnic group in Indonesia with varying degrees of myopia. Methods: A cross-sectional study was conducted at the Ophthalmology Clinic of Dr. M. Djamil General Hospital Padang from June to July 2024. The study involved 33 eyes from Minangkabau patients with myopia, categorized into three groups: mild, moderate, and high myopia. Axial length was measured using A-scan Biometry (immersion technique), and central corneal thickness (CCT) was assessed using Anterior Segment Optical Coherence Tomography (AS-OCT). Results: Significant differences were observed in the average values of AL and CCT among mild myopia (AL 23.93 ± 0.650 mm, CCT 530.45 ± 38.534 µm), moderate myopia (AL 25.03 ± 0.516 mm, CCT 518.64 ± 26.223 µm), and high myopia (AL 27.12 ± 1.524 mm, CCT 509.45 ± 30.422 µm) groups, with a p-value of 0.037 (p<0.05) and r = -0.729. A strong correlation between AL and CCT was found in individuals with myopia among the Minangkabau ethnic group (r = -0.729, p = 0.037). Conclusion: Higher degrees of myopia are associated with increased axial length and reduced central corneal thickness in the Minang ethnic group. These findings highlight the importance of considering ethnic differences in the assessment and management of myopia.